PENENTUAN JOB GRADING DI PT X - Lukito, Fulvian A.; Y.A., Debora Anne (Jurnal Titra, 2014)
PT X does not yet have the correct payrool system, so PT X wants to try to use the payrool system with job grading method. Job grading is a method for work grouping to determine the grade of a position based on the job description. Job grading method use several factors to evaluate position. These factors are know-how, area of responsibility, problem solving, and working condition. The result of job grading in PT X shows there are 4 levels: each level consisting of 2 sub levels. The result can be used in HR Department to determine employee salaries in PTX. There are 2 positions that are not in accordance with the name the of existing position. Both of these positions are head engineering and head of sales and marketing. Based on the level of difficulty of the work, both positions are equivalent to managerial level.